Sectoral Analysis Of Key Sectors Of Indian Markets Using Discounted Cashflow Valuations - Bathia, Amit; Jhaveri, Rushil; Baid,Sakhi; Bist,Drishti; Shelke, Gauri (Journal of Theoretical Accounting Research, 2025)
This study looks into the useand application ofthe discountedcash flow (DCF) method for valuingfirmsacross various industries.Whenvaluingacompany usingtheDCFmethod,futurecashflowsarepredictedandarisk-adjusteddiscount rateisappliedtoestimateintrinsicvalue.However,theeffectivenessofthismethodishighlydependentontheindustryin question.ThestudyanalyzesDCFvaluationsandmarketpricecomparisonsacrosssectorsincludingBankingandFinancial Services, Healthcare and Pharmaceuticals, Information Technology, Fast-Moving Consumer Goods (FMCGs), and Automobiles.ItisalsoworthmentioningthatHealthcareandespeciallytheITindustryaresectorswithstablerevenuesand, thus, more predictable cash flows. In contrast, the FMCG and Automobile industries contain more intangible assets and exhibitmorevolatilecashflowsonacyclicalbasis.TheFinancialServicesindustryalsohascashflowvolatilityduetodirect dependenceonregulatoryandeconomiccycles.Theprimary conclusionofsuchstudiespublishedisthatwhileDCF can capture value, the precision with which they do so is industry specific and in certain industries, a multi-model approach includingothermodelswillbe necessary tocapturethevalueofthefirm
ISME
Keywords: Discounted Cash Flow (DCF); Intrinsic Valuation; Sectoral Analysis; Valuation Accuracy; Sensitivity Analysis